OK!
3x - y = 13
2x +y = 12
Add the two equations together:
5x + 0y= 25
x=5
Now substitute x=5:
2 *(5) +y = 12
y=2
So, (x,y) = (5,2)
Done!
2007-01-15 12:51:56
·
answer #1
·
answered by Jerry P 6
·
1⤊
0⤋
Add the two equations. The y's cancel, leaving
5x = 25.
So x = 5 and y = 2.
2007-01-15 12:52:52
·
answer #2
·
answered by steiner1745 7
·
1⤊
0⤋
This isn't too difficult, hopefully you'll be able to figure it out.
It's C.
3(5) - (2) = 13
15 - 2 = 13
Equation one confirmed
2(5) + (2) = 12
10 + 2) = 12
Equation two confirmed. Hope I helped.
2007-01-15 12:54:10
·
answer #3
·
answered by gngerbreadmann 2
·
0⤊
0⤋
3x - y = 13
2x + y = 12
Add the two equations together and this will get you your x value.
5x = 25
x = 5
Therefore, the answer is C)
2007-01-15 12:51:17
·
answer #4
·
answered by Puggy 7
·
0⤊
0⤋
*Solve for "x" or "y" in either equation-let's solve for "y" in the 2nd equation...
First: subtract "2x" from both sides (moving variables to the opposite side means opposite sign)...
2x - 2x + y = 12 - 2x
y = 12 - 2x
Sec: replace "12 - 2x" with the "y" variable in the 1st equation...
3x - (12 - 2x) = 13
3x - 12 + 2x = 13
5x - 12 = 13
*Add 12 to both sides...
5x - 12 + 12 = 13 + 12
5x = 25
*Solve for "x" by isolating it on one side > divide both sides by 5...
5x/5 = 25/5
x = 5
Third: replace "5" with the "x" variable in the 2nd equation...
2(5) + y = 12
10 + y = 12
*Subtract 10 from both sides...
10 - 10 + y = 12 - 10
y = 2
The solution set is (5, 2)
2007-01-15 13:07:08
·
answer #5
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
5x= 25
x= 5
2(5)+y=12
y=2
C)(5,2)
2007-01-15 12:51:02
·
answer #6
·
answered by 7
·
1⤊
0⤋
C. (5,2) thanks for asking this...i have a geometry exam wednesday
2007-01-15 12:51:52
·
answer #7
·
answered by WaitingForAnswers 2
·
0⤊
1⤋
C
2007-01-15 12:51:57
·
answer #8
·
answered by Jack P 3
·
0⤊
1⤋
C
2007-01-15 12:51:44
·
answer #9
·
answered by abcde12345 4
·
0⤊
1⤋